Macroeconometric models - Welfe, Wladyslaw (Advanced Studies in Theoretical and Applied Econometrics, 2013)
This book gives a comprehensive description of macroeconometric modeling and its development over time. The first part depicts the history of macroeconometric model building, starting with Jan Tinbergen's and Lawrence R. Klein's contributions. It is unique in summarizing the development and specific structure of macroeconometric models built in North America, Europe, and various other parts of the world. The work thus offers an extensive source for researchers in the field. The second part of the book covers the systematic characteristics of macroeconometric models. It includes the household and enterprise sectors, disequilibria, financial flows, and money market sectors.